2013
DOI: 10.1590/s0103-51502013000100003
|View full text |Cite
|
Sign up to set email alerts
|

Variabilidade da frequência cardíaca como recurso em fisioterapia: análise de periódicos nacionais

Abstract: INTRODUÇÃO: O sistema nervoso autônomo (SNA) pode ser investigado de forma não invasiva a partir da análise da variabilidade da frequência cardíaca (VFC) e sua utilização para avaliação do SNA tem contribuído com várias áreas da saúde, dentre elas, a fisioterapia. OBJETIVOS: Reunir estudos publicados em periódicos de circulação nacional da área que abordassem a utilização da VFC em fisioterapia, a fim de fornecer uma atualização dos achados para a área. MATERIAIS E MÉTODOS: Foram selecionados, na lista de peri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
4

Year Published

2015
2015
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 28 publications
0
9
0
4
Order By: Relevance
“…This aspect has also been especially registered in the field of Speech-Language Pathology and Audiology that has an ever increasing number of scientific productions, certainly due to greater recognition of the field and to the increase in the number of Speech-Language Pathologists and Audiologists who are part of Graduate Studies Programs, for both Master's and Ph.D. degrees 5 . Scientific production analysis has been valued in surveys conducted in recent years [6][7][8][9][10][11][12][13][14][15] . Knowing the educational profile of the professionals in the field, their scientific production and their ability to educate future researchers help to build a picture of their current identity, and also to plan future scenarios.…”
Section: Methodsmentioning
confidence: 99%
“…This aspect has also been especially registered in the field of Speech-Language Pathology and Audiology that has an ever increasing number of scientific productions, certainly due to greater recognition of the field and to the increase in the number of Speech-Language Pathologists and Audiologists who are part of Graduate Studies Programs, for both Master's and Ph.D. degrees 5 . Scientific production analysis has been valued in surveys conducted in recent years [6][7][8][9][10][11][12][13][14][15] . Knowing the educational profile of the professionals in the field, their scientific production and their ability to educate future researchers help to build a picture of their current identity, and also to plan future scenarios.…”
Section: Methodsmentioning
confidence: 99%
“…This causes us to reflect on the neurophysiology of continence, which reaches the SNC afferently, signals returning efferent signals that regulate the ANS to maintain continence or to the onset of urination. Based on a systematic review 19 in Brazilian journals, it was observed that HRV is used in the scope of Physical Therapy as a resource for the evaluation of physiotherapeutic interventions, as a way of investigating pathological conditions common to clinical practice and for the interpretation of physiological conditions. Its use is made, mainly, by the cardiorespiratory specialty.…”
Section: Discussionmentioning
confidence: 99%
“…Desta forma, o estudo da modulação autonômica cardíaca por meio da variabilidade da frequência cardíaca (VFC) torna-se uma ferramenta importante para avaliar a integridade deste sistema [1,[4][5][6]. Além da análise da VFC, um teste autonômico de grande importância é a manobra de acentuação da arritmia sinusal respiratória (mASR).…”
Section: Introductionunclassified